Preparing for Local Labor: Curricular Stratification across Local Economies in the United States. (April 2017) - Sutton, April
I investigate how the educational demands of local labor markets shape high school course offerings and student course taking. Using the Education Longitudinal Study of 2002 linked to the U.S. Census 2000, I focus on local economic variation in the share of jobs that do not demand a bachelor's degree. I find that schools in local labor markets with higher concentrations of subbaccalaureate jobs devote a larger share of their course offerings to career and technical education (CTE) courses and a smaller share to advanced college-preparatory courses compared to schools in labor markets with lower concentrations of subbaccalaureate jobs, even net of school resources. Students in labor markets with higher concentrations of subbaccalaureate jobs take greater numbers of CTE courses, and higher-achieving students in these labor markets are less likely to take advanced math and Advanced Placement/International Baccalaureate courses. These course-taking disparities are largely due to school course offerings. This study shows how local economic inequalities shape high school curricular stratification, and suggests that school curricula linked to the educational demands of local jobs delimits the college preparation opportunities of high-achieving students.